Kakšne cilje si v programu delovne terapije postavljajo otroci s cerebralno paralizo? - Korelc, Simona (Rehabilitacija (Ljubljana), 2019)
Background: The goals of rehabilitation can be directed towards improving or restoring body structures and functions, functioning or participation. The latter is influenced by several factors in children with physical disabilities. The model of optimal participation includes a dynamic interaction between the individual characteristics of participation (child, family and environment) and dimensions of participation (physical, social and personality dimensions). We wanted to know which were the goals within occupational therapy of the children with cerebral palsy (CP) who had been involved in rehabilitation programs, and to which of the characteristics and dimensions of the cooperation model are these goals related. We were also wanted to find out whether the progress in achieving performance and satisfaction with the implementation of selected activities is linked to the capabilities of the gross movement of children with CP and their hand function. Methods: We analysed the data from randomly selected 40 children with cerebral palsy who were included in the inpatient rehabilitation program. We collected data on sex, age, degree of gross mobility, the level of hand function and the goals they have chosen in the occupational therapy program. Within the first hour, the children underlined difficulties in carrying out various activities by means of the Canadian Occupational Performance Measure (COPM), and then selected up to five goals with the help of parents and therapists. They used a visual analogue scale (grades 1 to 10) to assess how they perform an individual activity and how satisfied they are with the performance. The COPM evaluation was repeated at the end of the therapeutic program. Results: We included 16 boys and 24 girls (average age 9.9 years, SO 3.1). They were fairly evenly distributed according to the levels of the Gross Motor Function Classification System (GMFCS) and the Manual Ability Classification System (MACS). The children selected an average of 3.6 goals, or 51 different goals. Most of the selected goals were from the domain of basic, and less from the domain of extended daily activities, mobility, sports and school activities. The analysis of COPM scores showed a significant improvement in performance and satisfaction with the performance of all children combined as well as within individual GMFCS levels. We observed statistically significant differences between children in GMFCS levels I and II and other children. The children in level III advanced the most according to the COPM assessment of (the mean difference was 4.1 points). In the same group of children, we also found the largest difference in satisfaction with the implementation of the activity (the mean difference was 4.8 points). Conclusion: The analysis of the set goals showed that children with cerebral palsy, their parents and occupational therapists mostly choose goals from a set of basic daily-life activities, while they they are much less interested to improve more demanding skills in everyday activities, sports or school. The goal-oriented occupational therapy program is successful, which was confirmed by the improvement of performance and satisfaction ratings at the completion of the program. Improving performance and satisfaction with performance in children with cerebral palsy depends on the gross motor function and the manual function.
Keywords: Cerebral palsy; cerebralna paraliza; Child; goal setting; otrok; postavljanje ciljev; rehabilitacija; rehabilitation; vocational rehabilitation